Pelatihan UMKM Kopi Sebagai Upaya Untuk Meningkatkan Kualitas Usaha Di Desa Wonosalam - Bowo Santoso; Hallimah Rizqi Putti (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Coffee MSMEs in Wonosalam have started to develop but there is still relatively little promotion. Therefore, there is a need for training to improve the branding and quality of coffee cultivation, so that it becomes a successful business. UPN Veteran East Java organizes training assisted by Group 11 KKN-Thematic, this training includes several types, namely digital marketing, business development, and product packaging. The method used is lecture and discussion. With this training, coffee SMEs can understand how to develop their business through the use of technology in product marketing, get inspiration to develop new products, and can transform coffee businesses into branding and public awareness.